Diagnosis and management of chronic obstructive pulmonary disease in Serbia: an expert group position statement - Vukoja M; Kopitovic I; Lazic Z; Milenkovic B; Stankovic I; Zvezdin B; Dudvarski Ilic A; Cekerevac I; Vukcevic M; Zugic V; Hromis S (International Journal of COPD, 2019)
Marija Vukoja,1,2 Ivan Kopitovic,1,2 Zorica Lazic,3,4 Branislava Milenkovic,5,6 Ivana Stankovic,7,8 Biljana Zvezdin,1,2 Aleksandra Dudvarski Ilic,5,6 Ivan Cekerevac,3,4 Miodrag Vukcevic,6,9 Vladimir Zugic,5,6 Sanja Hromis1,21The Institute for Pulmonary Diseases of Vojvodina, Sremska Kamenica, Serbia; 2Faculty of Medicine, University of Novi Sad, Novi Sad, Serbia; 3Clinic for Pulmonology, Clinical Centre Kragujevac, Kragujevac, Serbia; 4Faculty of Medicine, University of Kragujevac, Kragujevac, Serbia; 5Clinic for Pulmonology, Clinical Centre of Serbia, Belgrade, Serbia; 6Faculty of Medicine, University of Belgrade, Belgrade, Serbia; 7Clinic for Lung Diseases, Clinical Centre of Nis, Nis, Serbia; 8Faculty of Medicine, University of Nis, Nis, Serbia; 9Clinical Hospital Centre Zemun, Belgrade, SerbiaCorrespondence: Marija VukojaCentre for Pathophysiology of Breathing and Sleep Medicine, The Institute for Pulmonary Diseases of Vojvodina, Put dr Goldmana 4 Street Sremska Kamenica 21204, SerbiaTel +381 21 480 5205Email marija.vukoja@mf.uns.ac.rsAbstract: In recent years, several national chronic obstructive pulmonary disease (COPD) guidelines have been issued. In Serbia, the burden of COPD is high and most of the patients are diagnosed at late stages. Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy is poorly implemented in real-life practice, as many patients are still prescribed inhaled corticosteroids (ICS)-containing regimens and slow-release theophylline. In this document, we propose an algorithm for treating COPD patients in Serbia based on national experts’ opinion, taking into account global recommendations and recent findings from clinical trials that are tailored according to local needs. We identified four major components of COPD treatment based on country specifics: active case finding and early diagnosis in high-risk population, therapeutic algorithm for initiation and escalation of therapy that is simple and easy to use in real-life practice, de-escalation of ICS in low-risk non-exacerbators, and individual choice of inhaler device based on patients’ ability and preferences. With this approach we aim to facilitate implementation of the recommendation, initiate the treatment in early stages, improve cost-effectiveness, reduce possible side effects, and ensure efficient treatment.Keywords: COPD, treatment, guidelines